Benign metastasizing leiomyoma presenting with miliary pattern and fatal outcome: Case report with molecular analysis & review of the literature. (2019) - Ofori, Kenneth; Fernandes, Helen; Cummings, Matthew; Colby, Thomas; Saqi, Anjali
Abstract: Benign metastasizing leiomyoma (BML) is a rare benign smooth muscle neoplasm that originates in the uterus and metastasizes to distant sites—most commonly the lungs. BMLs are often found incidentally in patients with a history of uterine leiomyoma(s) and tend to be indolent. Occasionally they may be symptomatic and rarely follow an aggressive clinical course. We report an unusual case of BML presenting in a 46-year-old woman as a miliary nodular pattern bilaterally in the lungs and progressive respiratory failure. Her past medical history was significant for uterine "leiomyomas" of at least 9 years' duration. Post mortem histologic evaluation of the uterine and lung lesions revealed benign smooth muscle neoplasms (leiomyomas and BMLs, respectively), and molecular analyses demonstrated identical clonal MED12 mutation, though with greater mutant allelic frequency in the uterus. We document a rare aggressive clinical course in a patient with BML, which presented as a miliary radiologic pattern mimicking an infectious etiology or interstitial lung disease.